Meningkatkan Softskill Presentasi Mahasiswa Politeknik Rukun Abdi Luhur - Tamara Jasmine; Iqbal Faza (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Presentation be a part of methode to support self-confidence. Presentation methode also applied in education’s sector since in elementary school until college. Presentation become an important to everyone, especially college student. Politeknik Rukun Abdi Luhur have a three study porgram major, where in the learning activities, the students not often got an assignment to presentation. There still is student who not understanding how to serving the presentation metter and make an interesting power point. The devotion starting from exposure the right presentation technic. In the middle activities, there is a presentation practice from two collage studenst. After that, exposure the second metter about how to make an interesting presentation material (power point). The result of this activites, students can doing the presentation as well as before and make an interesting power poit. With this devotion activities give a significant impact how students present and serve the material well. For the maximum result, students must keep present practice and make an interactive power point.